A quality of service load balanced stochastic diffusion search (TABU) search (TSDS) network backbone for manet - R.Kavitha, V.; Moorthi, M. (International Journal of Engineering and Technology, 2019)
The ad hoc network can present many different problems that influence a solution which can assure a proper quality of Service (QoS). The primary goal offered by the QoS was to ensure information delivery that was better and carried out by this network with a better network resource utilization. The main objective of the QoS routing found in the Mobile Ad hoc Network (MANET) was the optimization of the utilization of network resources when satisfying some application requirements. The AOMDV (the Ad hoc On-demand Multipath Distance Vector) and its routing protocol was a multipath extension of the protocol of AODV which aims at identifying a loop-free along with a link-disjoint multipath at the time of the process of route discovery. A Stochastic Diï¬€usion Search (SDS) will have a strong framework in mathematics that can describe the algorithm and its behaviour by means of investi-gating resource allocation, linear time complexity, minimal criteria of convergence, global optimum convergence and robustness. The TABU Search (TS) is a search strategy based on memory for guiding the method of local search in order to continue a search beyond the local optimum. For this work, there is a hybrid SDS along with the TS which is proposed for improving the QoS load balancing.Â